Taro in west Africa: status, challenges, and opportunities - Oladimeji, J.J.; Kumar, P. Lava; Abe, A.; Vetukuri, R.R.; Bhattacharjee, Ranjana (MDPI, 2022)
Taro is an ancient nutritional and medicinal crop woven into the fabric of the socio-economic life of those living in the tropics and sub-tropics. However, West Africa (WA), which has been a major producer of the crop for several decades, is experiencing a significant decline in production as a result of taro leaf blight (TLB), a disease caused by Phytophthora colocasiae Raciborski. A lack of research on taro in WA means that available innovative technologies have not been fully utilized to provide solutions to inherent challenges and enhance the status of the crop. Improvement through plant breeding remains the most economically and environmentally sustainable means of increasing the productivity of taro in WA. With this review, we provide insights into the importance of the taro crop in WA, evaluate taro research to date, and suggest how to address research gaps in order to promote taro sustainability in the region.